Artificial Intelligence Can Assist the Homeopath, But It Cannot Replace Him: Listening to a Doctor is Different from Listening to a Robot - Tarro, Giulio; De Giorgio, Giovanni (British Journal of Healthcare and Medical Research, 2025)
Homeopathy is a clinical methodology discovered about two centuries ago by the Saxon doctor Samuale Hahnemann, it is based on the law of similarities and treats the individual with a "small dose" of a specific substance that, in "high doses" would make him sick. The infinitesimal homeopathic doses are prescribed after a long medical visit during which the homeopath listens carefully to the patient’s narrative, takes into account the smallest narrative details, evaluates every kind of disorder accused by the patient and, based on the law of similarities, prescribes the appropriate, personalized, individualized homeopathic therapy. The attention paid to the patient, and not only to the disease, makes the narrative medical approach of classical homeopathy typical, which takes into account global, physical, mental and existential suffering. Listening homeopathically, therefore, means expanding listening based on a clear and precise motivation aimed at humanly understanding the overall meaning of pain. Generative AI, not having an internal motivation, is different from natural and human intelligence, that’s why the natural and well-motivated listening of a homeopath is very different from the artificial and unmotivated listening of a robot. To establish a natural and human relationship with the patient, one must listen naturally and humanely, but this does not exclude that the good use of artificial intelligence, in homeopathy, can prove extremely useful.